Aging Mechanisms of Electrode Materials in Lithium-Ion Batteries for Electric Vehicles. (21st June 2015) - Lin, Cheng; Tang, Aihua; Mu, Hao; Wang, Wenwei; Wang, Chun
Abstract : Electrode material aging leads to a decrease in capacity and/or a rise in resistance of the whole cell and thus can dramatically affect the performance of lithium-ion batteries. Furthermore, the aging phenomena are extremely complicated to describe due to the coupling of various factors. In this review, we give an interpretation of capacity/power fading of electrode-oriented aging mechanisms under cycling and various storage conditions for metallic oxide-based cathodes and carbon-based anodes. For the cathode of lithium-ion batteries, the mechanical stress and strain resulting from the lithium ions insertion and extraction predominantly lead to structural disordering. Another important aging mechanism is the metal dissolution from the cathode and the subsequent deposition on the anode. For the anode, the main aging mechanisms are the loss of recyclable lithium ions caused by the formation and increasing growth of a solid electrolyte interphase (SEI) and the mechanical fatigue caused by the diffusion-induced stress on the carbon anode particles. Additionally, electrode aging largely depends on the electrochemical behaviour under cycling and storage conditions and results from both structural/morphological changes and side reactions aggravated by decomposition products and protic impurities in the electrolyte.